Implementasi Gerakan Literasi Sekolah (GLS) Sebagai Upaya Meningkatkan Keterampilan Membaca Dan Menulis Di SMA Negeri 3 Batusangkar - Nella Mardiani; Sri Wahyuni (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2022)
This study aims to describe the form of implementation of the school literacy movement, the supporting and inhibiting factors and to determine the role of the library in the implementation of the GLS as an effort to improve reading and writing skills at SMA Negeri 3 Batusangkar.  The research method in this research is descriptive qualitative.  Data collection techniques in this study by observation, interviews, and documentation.  Data analysis techniques are data reduction, data display and conclusion drawing.  The validity of the data in this study used triangulation techniques, sources and lengthened observations. Results: The form of GLS implementation at SMA Negeri 3 Batusangkar is in the form of programs related to reading, writing and speaking literacy for students.  Supporting factors: active role of school community, program, students, support from parents and school committee, conducive school environment, facilities.  inhibiting factors: the consistency of the organizers, the condition of books that are starting to deteriorate due to age, and the limited number of collections of fiction books to support the School Literacy Movement in the literacy corner, not all students have the same interest and love for literacy, time allocation, and socialization of the GLS program.  The role of the library in the implementation of the GLS is that the library acts as a source of information, the library plays a role in collecting student work and preserving it, the library acts as a non-formal educational institution.